2020
DOI: 10.1126/sciadv.aay3909
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-mediated adhesions in regulation of cellular senescence

Abstract: Bioinformatic and functional data link integrin-mediated cell adhesion to cellular senescence; however, the significance of and molecular mechanisms behind these connections are unknown. We now report that the focal adhesion–localized βPAK-interacting exchange factor (βPIX)–G protein–coupled receptor kinase interacting protein (GIT) complex controls cellular senescence in vitro and in vivo. βPIX and GIT levels decline with age. βPIX knockdown induces cellular senescence, which was prevented by reexpression. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
(61 reference statements)
4
38
0
Order By: Relevance
“…Restoration of amphiphysin 1 rescued endocytic capacity in senescent cells ( Park et al, 2001 ), though its contribution to senescence was not established. A recent study found that the reduction in amphiphysin was due to its cleavage by calpain and that blocking this step inhibited senescence ( Shin et al, 2020 ). These results provided stronger support for reduced CME as a functionally important step in senescence.…”
Section: Clathrin-mediated Endocytosis In Senescencementioning
confidence: 99%
See 4 more Smart Citations
“…Restoration of amphiphysin 1 rescued endocytic capacity in senescent cells ( Park et al, 2001 ), though its contribution to senescence was not established. A recent study found that the reduction in amphiphysin was due to its cleavage by calpain and that blocking this step inhibited senescence ( Shin et al, 2020 ). These results provided stronger support for reduced CME as a functionally important step in senescence.…”
Section: Clathrin-mediated Endocytosis In Senescencementioning
confidence: 99%
“…This process also involves microtubule targeting ( Ezratty et al, 2005 ), integrin endocytosis ( Chao and Kunz, 2009 ; Ezratty et al, 2009 ) and calpain-mediated proteolysis of FA proteins ( Chan et al, 2010 ; Cortesio et al, 2011 ; Franco et al, 2004 ). Analysis of these proteins in senescent cells revealed a new link between these events ( Shin et al, 2020 ). First, to understand whether reduced βPIX expression contributes to the senescent phenotype, both loss-of-function and gain-of-function studies were performed.…”
Section: Clathrin-mediated Endocytosis In Senescencementioning
confidence: 99%
See 3 more Smart Citations